Analisis efektifitas pada integrasi NIK menjadi NPWP terhadap tingkat kepatuhan pajak dalam konteks akuntansi perpajakan (studi kasus KPP Pratama Jember) - Maulidia, Anisa; Makkiyah; Sari, Putri Aprilia; Fatimatuzzahro (Journal of Economics, Business, Accounting and Management, 2023)
In realizing the increase in taxes, many obstacles are faced so that the level of tax compliance is still minimal, which results in taxpayers trying to pay less tax than they should. There are still many taxpayers who do not report and pay taxes. This has caused the government to establish regulations on the integration of Population Identification Numbers (NIK) into Taxpayer Identification Numbers (NPWP) with the Single Identity Number (SIN) system in increasing mandatory compliance, which has been regulated in Minister of Finance Regulation Number 112/PMK.03/2022 concerning Numbers. Tax Principals for individual taxpayers, corporate taxpayers and government agency taxpayers. This research uses qualitative methods derived from literature studies, in addition to using primary data, namely data taken by conducting direct interviews with Jember Pratama Tax Service Office (KPP) employees regarding tax revenues from January to August from 2022 to 2023 In the policy of integrating the Population Identification Number (NIK) into a Taxpayer Identification Number (NPWP) or what is called the Single Identity Number (SIN) system. This policy has a positive impact so that there is no need to have a lot of identification for various purposes, so that taxpayers find it easy to do this and increase taxpayer compliance. Furthermore, the Jember Pratama Tax Services Office (KPP) implemented strategies as an effort to increase taxpayer compliance, including education and outreach, improving services, use of technology, law enforcement, and collaboration with related parties.